2022
DOI: 10.1136/bmjopen-2021-056667
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of depression in China during the early stage of the COVID-19 pandemic: a cross-sectional study in an online survey sample

Abstract: ObjectivesWe aimed to determine (1) the prevalence of depression during the COVID-19 pandemic among Chinese adults and (2) how depression prevalence varied by province and sociodemographic characteristics.DesignCross-sectional study.SettingNational online survey in China.ParticipantsWe conducted a cross-sectional online survey among adults registered with the survey company KuRunData from 8 May 2020 to 8 June 2020. We aimed to recruit 300–360 adults per province (n=14 493), with a similar distribution by sex a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 45 publications
1
7
0
Order By: Relevance
“…Previous survey studies in China revealed that the prevalence of anxiety or depression among cancer patients during COVID-19 pandemic was about 15.5% to 39.7%, compared with 6.3% depression rate among general population in China during this period [8,[18][19][20]. In our study, the proportion of patients who reported experiencing sadness or depression was 30.7%, which was consistent with previous ndings.…”
Section: Discussionsupporting
confidence: 91%
“…Previous survey studies in China revealed that the prevalence of anxiety or depression among cancer patients during COVID-19 pandemic was about 15.5% to 39.7%, compared with 6.3% depression rate among general population in China during this period [8,[18][19][20]. In our study, the proportion of patients who reported experiencing sadness or depression was 30.7%, which was consistent with previous ndings.…”
Section: Discussionsupporting
confidence: 91%
“…There have been studies on the aetiology of depression (Chen et al, 2022 ; Durisko et al, 2015 ; Saveanu & Nemeroff, 2012 ), which is the most common mental health disorder in the general population (Lim et al, 2018 ). Efforts have been made in line with this during the pandemic (Hajek et al, 2022 ; Liu et al, 2022 ). According to the cognitive approach, a dysfunctional belief system may be effective in the development of depression (Beck, 1995 ).…”
Section: Introductionmentioning
confidence: 99%
“…Prefecture tier level A higher level of urbanization was found to be associated with poor mental health during the COVID-19 pandemic in China (Liu et al, 2022), as the virus may be transmitted quickly in urban areas with more economic activities and population density. We controlled for urbanization by using China's prefecture tier system.…”
Section: Educationmentioning
confidence: 99%